Nitrosylation of Hexafluoridotechnetate(IV). Issue 5 (28th March 2013) - Mariappan Balasekaran, Samundeeswari; Molski, Matthias; Hagenbach, Adelheid; Abram, Ulrich
Abstract Potassium hexafluoridotechnetate(IV), K2[TcF6], slowly reacts in aqueous solution with acetohydroxamic acid with formation of the ammine nitrosyltechnetium(I) complex [Tc(NO)(NH3)4F]+. The product crystallizes as mixed TcF62–/HF2– salt of the composition [Tc(NO)(NH3)4F]4[TcF6][HF2]2. [Tc(NO)(NH3)4F]+ represents the first nitrosyltechnetium complex with a fluorido ligand in its coordination sphere. The Tc–F bonds in two crystallographically independent species are 1.987(2) and 2.034(2) Å, respectively. This is slightly longer than in the [TcF6]2– counterion.